Pengaruh E-Commerce Terhadap Tingkat Penjualan Kangkung Rendang Pada UMKM Syifa Hidroponik - Rahman, Sultan Arif; Ilvira, Rika Fitri (Universitas Medan Area, 2025)
Kangkung rendang is an innovative processed product produced from hydroponic kale, providing added value and increasing producer income. This study aims to analyze the effect of e-commerce usage on increasing sales of kale rendang at Syifa Hidroponik MSMEs. The study uses quantitative methods with simple linear regression analysis to measure the effect of e-commerce. This study uses primary data conducted by means of surveys and interviews with consumers, the number of respondents in this study was 30 respondents. Data were analyzed with the help of SPSS Software. The results showed that the use of e-commerce significantly increased the effectiveness of marketing and sales of kale rendang products, thus having a positive impact on MSME income. t-hit and Sig. (p-value): Shows the statistical significance of the coefficient. If the p-value 0.05, then it can be said that the effect of e-commerce on sales is significant. Therefore, the data in this study is significant and e-commerce has an effect on increasing sales because the value of E-Commerce (X) in Sig. (p-value) is 0.002.